Bafetinib Suppresses the Transcription of PD-L1 Through c-Myc in Lung Cancer - Chen, Xi; Du, Qianqian; Guo, Hongjie; He, Qiaojun; Yang, Bo; Ding, Ling (Frontiers in Pharmacology, 2022)
Given the limitations of the existing antibody-based therapies, including immune-related adverse events, poor response rates and intravenous route of dosing, small molecules inhibitors targeting PD-L1 are highly desirable. By cell-based screening, we found that tyrosine kinase inhibitor Bafetinib dramatically suppresses PD-L1 protein expression in a dose-dependent manner. In parallel, cell membrane PD-L1 is also reduced by Bafetinib. We confirm that Bafetinib doesn’t affect the protein half-life of PD-L1 but significantly inhibits the transcription of PD-L1. Among the transcription factors that regulate PD-L1 expression, c-Myc is downregulated by Bafetinib. Bafetinib caused PD-L1 inhibition is abolished when c-Myc is knocked-down. Further, we identified that Bafetinib reduced c-Myc expression because of transcription inhibition. By using CT26 tumor model, we further confirm that Bafetinib suppressed PD-L1 expression in vivo. In conclusion, our study shows that Bafetinib inhibit the transcription of PD-L1 through transcription factor c-Myc, suggesting that Bafetinib might be a small molecule drug targeting PD-L1.